(3JMQjQ GdCMcGe aj JOHjQ Ggd GdGSdGes - (3HOQ GdOjf eMeO Hf EHQGgje Hf SYO Gddg Hf LeGYI GdcfGfj,J (B740 (3g` s ((3ffeQHGi (B( (3ef Mce Hf WjaQ GdZhQ s)
(3ChdgG (B:s
(3GdMeO ddg Ydi fYeI GdHGWfI hGdXGgQI hgPG eNJUQ ai Led ef GdGMcGe GdSdWGfjI hfHP ef GdbhGYO GdGSdGejI hPcQ GehGd HjJ GdeGd s
(3BNQgG (B:s
(3hbGd CMeO jNjQ GdEeGe ajg Hjf GdbJd hGdGSJQbGb hddTGaYi bhd Gfg jQO Edi eCefg Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI NRGFfjI HQSe GdSdWGf GdCTQa NGf HdGW s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
Keywords: (3eJaQbGJs